Breeding for intercrops with special attention to beans for intercropping with maize - Davis, J. (International Center for Tropical Agriculture, 1989)
Some methodologies, including examples, for developing bean var. specifically adapted to intercropping with maize are considered. Since every breeding program has to contend with genotype x environment interactions, decisions have to be made regarding the locations for breeding nurseries, the conditions of soil fertility, and disease and pest control. For bush beans, the interaction between genotypes and cropping systems (monocrop vs. maize intercrop) is usually slight, whereas for indeterminate beans, the interaction is often highly significant. Traits such as time of maturity, plant type, tolerance to soil constraints, and disease and pest resistance are analyzed; these should be considered for intercropping. Single plant selection of beans is normaly best done in monocrop except in climbing beans, since it is simpler and cheaper to plant with maize (1 bean plant to 1 maize plant). The early generation evaluation of the progeny is usually better done in monocrop; however, climbing beans are readily evaluated with maize. Early generation yield trials have been found to be effective. HI may be a valid selection criterion for breeding programs aiming at improving intercrop efficiency. Plans for on- farm trials can be developed through joint farmer- researcher discussion, which is especially relevant for research on cropping systems. (CIAT)